2012
DOI: 10.1007/s00280-012-1825-y
|View full text |Cite
|
Sign up to set email alerts
|

Midostaurin does not prolong cardiac repolarization defined in a thorough electrocardiogram trial in healthy volunteers

Abstract: PurposeMidostaurin (PKC412) is a multitargeted tyrosine kinase inhibitor of FMS-like tyrosine kinase 3 receptor (FLT3), c-KIT, and other receptors. Midostaurin is active in patients with acute myeloid leukemia and systemic mastocytosis. Although no substantive risk for cardiac abnormalities has been observed with midostaurin in clinical studies thus far, some TKIs have been shown to affect cardiac repolarization. Here we evaluated midostaurin’s effect on cardiac repolarization.MethodsThis phase I study evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
2
14
0
1
Order By: Relevance
“…The slope describing the relationship between QTcF interval versus moxifloxacin concentrations was 3.1 ms/μg mL –1 , consistent with that observed in other thorough QT studies and confirming an exposure–response effect of moxifloxacin on QTcF. 29 31 As moxifloxacin exposure was considerably lower in this study than reported in the literature, 30 PK/PD modeling was conducted to assess the predicted effect of higher moxifloxacin concentrations on ΔΔQTcF. One thousand datasets were simulated based on doubling the individual concentrations at each time point in the original dataset so as to be similar to those in the typical range observed in other studies reported in the literature.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The slope describing the relationship between QTcF interval versus moxifloxacin concentrations was 3.1 ms/μg mL –1 , consistent with that observed in other thorough QT studies and confirming an exposure–response effect of moxifloxacin on QTcF. 29 31 As moxifloxacin exposure was considerably lower in this study than reported in the literature, 30 PK/PD modeling was conducted to assess the predicted effect of higher moxifloxacin concentrations on ΔΔQTcF. One thousand datasets were simulated based on doubling the individual concentrations at each time point in the original dataset so as to be similar to those in the typical range observed in other studies reported in the literature.…”
Section: Resultssupporting
confidence: 89%
“…Administration of moxifloxacin with food decreased both the rate and extent of absorption as evidenced by the lower C max and AUC values for moxifloxacin in comparison to literature values for moxifloxacin obtained in the fasted state. 29 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In a phase I study of midostaurin in healthy young volunteers, midostaurin was not shown to cause prolongation of cardiac repolarization. 35…”
Section: Cardiotoxicitymentioning
confidence: 99%
“…随后药物化学家对其进行结构改造, 多个衍 生物已经作为抗肿瘤药物进入了临床研究 [19] . 多靶点 的蛋白激酶抑制剂 PKC-412 [20] 可以有效抑制人白血病 细胞的增殖 [21] , 在临床 I 期研究中表现出了安全性和有 效性 [22] . 临床 II 期研究结果表明, PKC-412 对 FMS 样酪 氨酸激酶 3 (Flt-3)突变型和野生型的急性骨髓性白血病 受试者均有效 [23] .…”
Section: Zhang Yapengunclassified